2013
DOI: 10.2478/pomr-2013-0040
|View full text |Cite
|
Sign up to set email alerts
|

Test research on the resistance performance of high-speed trimaran planing hull

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Trimarans have wide naval applications and for civil transportation provide such outstanding advantages as: lower levels of resistance at high speed, good seakeeping performance and a comparatively wide deck compared with mono-hull and catamaran hull forms. The published research addresses: strength (Wu et al, 2011b;Zhen et al, 2012) and resistance (Ma et al, 2013) of the high speed trimaran, good seakeeping performance (Davis and Holloway, 2007) and multi-hull configuration optimisation (Zhang and Han, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Trimarans have wide naval applications and for civil transportation provide such outstanding advantages as: lower levels of resistance at high speed, good seakeeping performance and a comparatively wide deck compared with mono-hull and catamaran hull forms. The published research addresses: strength (Wu et al, 2011b;Zhen et al, 2012) and resistance (Ma et al, 2013) of the high speed trimaran, good seakeeping performance (Davis and Holloway, 2007) and multi-hull configuration optimisation (Zhang and Han, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Ghassabzadeh and Ghassemi developed an innovative method for the parametric design of a planing tunnel vessel, and numerical and experimental research on its resistance performance was also performed [9,10]. Ma et alconducted a series of model tests to investigate the resistance and sea keeping performance of a planing trimaran, in which step was introduced on main hull bottom to reduce the high-speed resistance, and the effect of hydrofoil and bilge keel in the tunnel region were also tested [11,12]. Su et al experimentally investigated the planing trimaran as well, the following numerical results were focused on the influence of the longitudinal location of a gravity center and displacement on resistance [13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, using underwater photographs, White et al 10 reported the effects of step location and step height on wetted surface. Systematic experimental studies of the stepped planing hull series have been conducted by Morabito et al, 3 Lee et al, 4 Ma et al 11 and Taunton et al 12 Besides the mentioned experimental studies, mathematical models have also been used to model nonstepped/stepped planing hulls. 13,14 Some of these mathematical methods have been established by using the 2D + T method, where the results of water entry of a wedge [15][16][17] are used to simulate motion of planing hulls in both calm water and waves (see, for example, Tavakoli et al, 14 Tavakoli and Dashtimanesh 15 and Ghadimi and colleagues [18][19][20][21] ).…”
Section: Introductionmentioning
confidence: 99%